Ответы и объяснения

2013-02-13T20:03:59+04:00

x^2/x^2-9=12-x/x2-9 |*x^2-9 (не равно нулю) (приводим к общему знаменателю)

знаменатель убирается,получаем:

x^2=12-x (переносим)

x^2+x-12=0 (по теореме Виетта) | x^2+x-12=0

                                                               [x=-4

                                                               [x=3

делаем проверку

Если x=3,то x^2-9=3^2-9=0(н)

Если х=-4,то x^2-9=(-4)^2-9=0(в)

Ответ:-4

 

2013-02-13T20:36:43+04:00

x^2/x^2-9=12-x/x2-9 |*x^2-9 (приводим к общему знаменателю)

x^2=12-x

x^2+x-12=0 

D=1+48=49=7^2

x1=-1+7|2=3

x2= -1-7|2=-4

делаем проверку

Если x=3,то x^2-9=3^2-9=0(неверно)

Если х=-4,то x^2-9=(-4)^2-9=0(верно)

Ответ:-4